Acute liver injury in the course of lymphoplasmacytic lymphoma - Kuzemko-Baranowska, Dorota; Baranowski, Dariusz; Prystupa, Andrzej (Current Issues in Pharmacy and Medical Sciences, 2019)
Non-Hodgkin lymphomas are malignant neoplasms whose incidence rates increase each year. These also include neoplasms rare in the general population. The present case report described a patient with lymphoplasmacytic lymphoma (LPL) and rapid liver damage. In most cases, infiltration of the liver is rare in advanced stages of hematopoietic malignancies when hepatomegaly, cholestatic jaundice and organ failure are observed. The patient’s history includes non-specific abdominal pain that was accompanied by general symptoms such as nocturnal hyperhidrosis, subfibrile temperature and fever, as well as weight loss. The above complaints aggravate with an increase in organ size. The laboratory findings initially demonstrated moderately elevated concentrations of transaminases. In our case, the baseline biochemical indices of liver function were found to be normal. During the next days of hospitalisation, the features of liver damage intensified and were accompanied by liver failure. The gold diagnostic standard is a biopsy of the bone marrow and the organ affected. Since the patient’s condition deteriorated and liver failure developed, the diagnosis was established based on trephine biopsy of the bone marrow. Chemotherapy was implemented; despite the treatment applied, the patient’s clinical condition did not improve. Two months after the onset of first symptoms the patient died.